2014
DOI: 10.1113/jphysiol.2014.279380
|View full text |Cite
|
Sign up to set email alerts
|

Misinterpretation of the mouse ECG: ‘musing the waves of Mus musculus

Abstract: The ECG is a primary diagnostic tool in patients suffering from heart disease, underscoring the importance of understanding factors contributing to normal and abnormal electrical patterns. Over the past few decades, transgenic mouse models have been increasingly used to study pathophysiological mechanisms of human heart diseases. In order to allow extrapolation of insights gained from murine models to the human condition, knowledge of the similarities and differences between the mouse and human ECG is of cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
116
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(127 citation statements)
references
References 89 publications
11
116
0
Order By: Relevance
“…AP recordings in WT mice demonstrated a higher V max and APD in myocytes from subendocardium compared with subepicardium (P<0.05; Figure 4A and 4C). These transmural differences were diminished in Hey2 +/− mice (Figure 4B and 4D; P<0.05 interaction effect for V max and APD 90 ; P=0.1 and P=0.07 interaction effect for APD 20 and APD 50 , respectively) because of an increase in subepicardium in Hey2 +/− compared with WT mice (P<0.01 for V max , APD 20 , APD 50 , and APD 90 ; Online Table IV). Heterozygous loss of Hey2, thus, affects both depolarization and repolarization specifically in the subepicardium layer.…”
Section: Hey2 Affects Repolarization and Depolarization Specifically mentioning
confidence: 99%
See 2 more Smart Citations
“…AP recordings in WT mice demonstrated a higher V max and APD in myocytes from subendocardium compared with subepicardium (P<0.05; Figure 4A and 4C). These transmural differences were diminished in Hey2 +/− mice (Figure 4B and 4D; P<0.05 interaction effect for V max and APD 90 ; P=0.1 and P=0.07 interaction effect for APD 20 and APD 50 , respectively) because of an increase in subepicardium in Hey2 +/− compared with WT mice (P<0.01 for V max , APD 20 , APD 50 , and APD 90 ; Online Table IV). Heterozygous loss of Hey2, thus, affects both depolarization and repolarization specifically in the subepicardium layer.…”
Section: Hey2 Affects Repolarization and Depolarization Specifically mentioning
confidence: 99%
“…Of note, this observation was consistent in both lead I and II ( Figure 3A), and the difference in J-wave derivative between WT and Hey2 +/− was independent of lead (2-way ANOVA). Because the murine J wave is an expression of early repolarization 20 ; this indicated that early repolarization may differ between the WT and Hey2 +/− animals. To further investigate this, we recorded APs from cardiomyocytes isolated from the subepicardium and subendocardium of the RV (implicated in the pathophysiology of BrS [21][22][23] ) from both WT and Hey2 +/− mice (Figure 4A and 4B; Online Table IV).…”
Section: Hey2 Affects Repolarization and Depolarization Specifically mentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac activity is known to differ between humans and experimental animals. Beating rate and electrocardiogram results differ greatly between species, as do the molecular mechanisms of repolarization and expression of various genes and proteins (Boukens et al, 2014;Denning et al, 2016). These cause differences in each species' tolerance to chemical agents (Price et al, 2008), and might yield false-positive or -negative results when human toxicity is evaluated using experimental animals and cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac hazards, such as the threshold value for ventricular fibrillation, have been evaluated by magnetic or electrical stimulation of experimental animals (Elmas et al, 2012;Fozzard and Schoenberg, 1972;Mouchawar et al, 1989), and data from animal studies have been applied to humans after adjusting for body size (Geddes et al, 1973). However, theoretical models are limited in their ability to predict human responses, as it is known that many aspects of fundamental cardiac activity, such as beating rate and electrocardiogram results (Boukens et al, 2014;Denning et al, 2016), differ between species. Although some human studies have been reported, the strength of EMF exposure was sufficiently low to be safe (Cook et al, 1992;Korpinen et al, 1993;Graham et al, 1994;Korpinen and Partanen, 1994), and limited experimental data are available for direct evaluation of human effects.…”
Section: Introductionmentioning
confidence: 99%